The relationship between charge density and polyelectrolyte brush profile using simultaneous neutron reflectivity and in situ attenuated total internal reflection FTIR - Topham, Paul D (Langmuir : the ACS journal of surfaces and colloids, 2013)
We report on a novel experimental study of a pH-responsive polyelectrolyte brush at the silicon/D2O interface. A poly[2-(diethylamino)ethyl methacrylate] brush was grown on a large silicon crystal which acted as both a substrate for a neutron reflectivity solid/liquid experiment but also as an FTIR-ATR spectroscopy crystal. This arrangement has allowed for both neutron reflectivities and FTIR spectroscopic information to be measured in parallel. The chosen polybase brush shows strong IR bands which can be assigned to the N-D(+) stretch, D2O, and a carbonyl group. From such FTIR data, we are able to closely monitor the degree of protonation along the polymer chain as well as revealing information concerning the D2O concentration at the interface. The neutron reflectivity data allows us to determine the physical brush profile normal to the solid/liquid interface along with the corresponding degree of hydration. This combined approach makes it possible to quantify the charge on a polymer brush alongside the morphology adopted by the polymer chains